Analyzing key influences of tourists’ acceptance of online reviews in travel decisions - Chong, Alain Yee Loong; Khong, Kok Wei; Ma, Teng; McCabe, Scott; Wang, Yi (Emerald, 2018)
Purpose: This study aims to examine what influence travelers’ adoption of online reviews, and whether the online reviews will influence their travel planning decisions. Design/methodology/approach: Data was collected from 193 respondents from eWOM websites and analyzed using structural equation modeling. Findings: Our results revealed that eWOM has a significant influence on travel decisions. Furthermore, travelers were willing to adopt information from eWOM and this information was useful in their travel planning and decisions. Gender and time spent on online reviews were found to affect travel planning and decisions. Travelers also found that the reviews and issues raised in eWOM had credibility and were of good quality. Research limitations/implications: Our study was not able to incorporate all factors which may be relevant to this study and so further theoretical development may be necessary to develop the conceptual model. The sample size, while adequate, can be expanded further. Practical implications: Operators and administrators of eWOM can use these findings to develop more user-friendly interfaces so that more positive reviews and sales can be generated. Social implications: Our results showed that travelers who adopt the information in eWOM will, in turn, use eWOM in their travel planning. This confirms the importance of eWOM and travelers in general will translate their pre-travel decisions into actual travel planning. Originality/value: This research extended existing eWOM and information system adoption studies and focused on the travel planning context. This research validated the significant roles of eWOM argument quality and credibility in predicting the information usefulness of eWOM.